Impact of dehydroepiandrosterone on clinical outcome in poor responders: A pilot study in women undergoing in vitro fertilization, using bologna criteria - Jirge, Padma Rekha (J Hum Reprod Sci, 2014)
OBJECTIVE: To evaluate the role of dehydroepiandrosterone (DHEA) supplementation in women with poor ovarian response (POR) undergoing in vitro fertilization (IVF). DESIGN: Prospective case-control study. SETTING: Private tertiary fertility clinic. MATERIALS AND METHODS: 31 infertile women with POR diagnosed as per the Bologna criteria. INTERVENTIONS: DHEA supplementation for 2 months and a subsequent IVF cycle, after two previous IVF cycles with POR. MAIN OUTCOME MEASURE(S): Dose and duration of gonadotropin therapy, oocyte yield, embryo number and quality, pregnancy and live birth rate. RESULTS: No difference was seen in gonadotropin requirement before and after DHEA supplementation. There was a significant increase in total and metaphase II oocytes (5.9 ± 0.68 vs. 2.73 ± 0.24; 4.45 ± 0.47 vs. 2.09 ± 0.26), fertilization (3.65 ± 0.49 vs. 2.00 ± 0.27), Grade I embryos (1.52 ± 0.25 vs. 0.55 ± 0.18), pregnancy rate (30% vs. 9.1%) and live birth rate (25% vs 0%) in those who completed the cycle, following DHEA supplementation. CONCLUSIONS: Dehydroepiandrosterone supplementation results in an improvement in oocyte yield, embryo quality, and live birth rate in a group of women with POR having undergone at least two previous failures due to POR.